PENGARUH KOMUNIKASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA DPS (DAPUR PANGAN SEJAHTERA) CATERING JAKARTA TAHUN 2018 - Agus Riyanto; Dwi Eny Susilowati (Human Capital Development, 2018)
Purpose- This study aims to determine and analyze the influence of Communications (X1), motivation (X2) and the Working Environment (X3) the Employee Performance (Y) DPS Catering Jakarta. Design/methology/approach- The population in this study are entire employee at DPS Catering Jakarta in July 2018. The sampling technique used is non probability sampling, by saturated sample method to determine 100 respondents. Method of data collection using questionnaires that has been tested its validation and reliability. The method of analysis using Clasic test, prior to Multiple Linear Regresion by SPSS 20,0 as a tool, followed by f test; t test; Coorelation, and Determination tests. Findings- The results proved that partially, Communication variables have a positively effect on employee performance, Motivation variables have a positively effect on employee performance, work environment variables have a positively effect on employee performance partially. Hence, all of the variables are positively effected employee performance at DPS Catering Jakarta